Registration of eleven local varieties of rice and beans distributed by more than 3,000 farmers in Nepal - CGIAR Research Program on Policies, Institutions, and Markets (2020)
With PIM support, Bioversity International and partners provided technical and policy support for the registration process for local varieties in Nepal and assisted farmers' associations in submitting registration proposals, leading to registration of eleven varieties of rice and beans. 3,000 farmers and eight farmers’ cooperatives are already engaged in the distribution of these varieties, generating enhanced benefits for farming communities and increased crop diversity.